First-Line Anti-Tuberculosis Drug Resistance Pattern - Ayurveda Zaynabila Heriqbaldi; Rebekah Juniati Setiabudi; Resti Yudhawati (Jurnal Respirasi, 2022)
Introduction: An important concern regarding TB currently is the case of anti-TB drug resistance; hence research on resistance patterns and risk factors is essential. This study aimed to identify the pattern of first-line anti-TB drug resistance. Methods: This descriptive retrospective study was conducted at MDR-TB polyclinic Dr. Soetomo General Hospital, Surabaya, in 2017-2019. Only complete medical records were included. The variables were first-line anti-TB drug resistance (isoniazid, rifampicin, ethambutol, streptomycin) and patients’ characteristics (age, gender, treatment history, and comorbidities). The drug resistance test was performed using certified culture methods. Results: Among 239 patients, the incidences of resistance to H, R, E, and S were 79.08%, 94.14%, 25.94%, and 20.08%, respectively. The most common patterns were HR (42.26%), R (18.83%), and HRE (12.55%). The largest age group was 45-54 years old (38%). The dominant gender was male (56.49%). The most treatment history category was relapsed patients (48%) and there were more patients with comorbidity (57%). Conclusion: The highest incidence rate of resistance was rifampicin and the most common resistance pattern was HR. Most of the patients were of working age, male, relapse patients, and had comorbidities. An appropriate TB therapy treatment plays an important role in preventing resistance.